Investigation of washout and rainout processes in sequential rain samples. (October 2018) - Bayramoğlu Karşı, Melike Büşra; Yeni̇soy-Karakaş, Serpil; Karakaş, Duran
Abstract: In this study rainfall events were sampled sequentially between April and June 2014 (one event in April, two in May and one in June 2014) in the city center of Bolu province located in the western Black Sea Region of Turkey. Particle size distributions, pHs, major ion compositions and fractional distributions, neutralization factors and washout, rainout identifications were investigated by evaluating the data obtained from the sequences of the rain events. Local wind directions and upper atmospheric three dimensional back trajectory calculations were also used to identify the source regions affecting the receptor site. The primary purposes of this study were to present the effectiveness of washout and rainout processes and to identify the contributions of local and distant source regions to the rainfall events affecting the north western part of Turkey. The average pH values for the subsamples were determined as 5.20 ± 0.47, 5.51 ± 0.21, 6.97 ± 0.23 (6.66–7.20) and 6.42 ± 0.16 (6.17–6.66), respectively for the four rain events sampled. Ninety percent of the particles were smaller than 1135 μm for the first fraction, 444, 5 μm for the second fraction, and 0.79 μm for the third fraction, respectively. Except for the fourth fraction, sequences of the rain event showed a linear decrease in particle sizes. The highest rainout to washout ratios were observed for nitrate ion (72.4%) and followed by ammonium ion (63.5%), chloride (48.4%), sulfate (46.3%), magnesium ion (41.5%), and potassium ion (31.2%). Strong correlations of nitrate and sulfate with Ca 2+, Mg 2+ and Na + suggested that the rain droplets were neutralized by these alkaline ions. Highlights: Rain events affected by dust incursions carries high levels of calcium. Particles greater than 1.0 μm are removed with the first and the second sequences. Rainout and washout contributions to total deposition can be calculated. For arid and semi-arid regions calcium is the dominant neutralizer. Anionic deficiencies are observed in rainfalls affected by dust incursions.